Quenching of O2(b1Σg+) by O(3P) atoms. Effect of gas temperature. (1st June 2022) - Booth, J P; Chatterjee, A; Guaitella, O; Lopaev, D; Zyryanov, S; Volynets, A; Rakhimova, T; Voloshin, D; Chukalovsky, A; Mankelevich, Yu.; Guerra, V
Abstract: We present a detailed study of the density and kinetics of O2 (b 1 Σg + ) in steady-state and partially-modulated DC positive column discharges in pure O2 for gas pressures of 0.3–10 Torr and 10–40 mA current. The time-resolved density of O2 (b 1 Σg + ) was determined by absolutely-calibrated optical emission spectroscopy (OES) of the A-band emission at 762 nm. Additionally, the O2 (b 1 Σg + ) density was determined by VUV absorption spectroscopy using the Fourier-transform spectrometer at the DESIRS beamline at Synchrotron Soleil, allowing the absolute calibration of OES to be confirmed. The O( 3 P) atoms were detected by time-resolved sub-Doppler cavity ringdown spectroscopy (CRDS) using the O( 3 P2 ) → O( 1 D2 ) transition at 630 nm. The CRDS measurements were synchronized to the discharge modulation allowing the O( 3 P) dynamics to be observed. As a function of gas pressure the O2 (b 1 Σg + ) density passes through a maximum at about 2 Torr. Below this maximum, the O2 (b 1 Σg + ) density increases with discharge current, whereas above this maximum it decreases with current. The gas temperature increases with pressure and current, from 300 to 800 K. These observations can only be explained by the existence of fast quenching process of O2 (b 1 Σg + ) by O( 3 P), with a rate that increases strongly with gas temperature, i.e. with a significant energy barrier. The data are interpreted using a 1D self-consistent model of the O2 discharge. The best fit of this model to all experimental data (including the O2 (b 1 Σg + ) average density as a function of pressure and current, the radial profiles, and the temporal response to current modulation) is achieved using a rate constant of k Q = 10 −10  exp(−3700/ T ) cm 3  s −1 .